Authorship in science: A critical analysis from a Foucauldian perspective - Hilário, Carla Mara [UNESP]; Martínez-Ávila, Daniel [UNESP]; Grácio, Maria Cláudia Cabrini [UNESP]; Wolfram, DIetmar (Oxford University Press (OUP), 2018)
This article aims to contribute to the discussion on authorship in contemporary science from Foucauldian and Kuhnian perspectives, highlighting the social aspects of science and the role of authorship in scientific revolutions. Thus, it describes the functions of the 'author' discussed by Foucault that can assist to reveal the characteristics of the scientific practice and examples of how theories are materialized. As a result, it identifies the ways in which modern science is developed and how knowledge is construed by multiple authors, group authors, the merit that is attributed by citations, etc. This article highlights the complexity of authorship attribution and the need to rethink generalized bibliometric techniques to evaluate science considering other aspects that go beyond the mere listing of the authors.
Keywords: authorship; Foucault; Kuhn; scientometrics; sociology of science